Metagenomic Investigation Uncovers Presence of Probiotic-Type Microbiome in Kalparasa® (Fresh Unfermented Coconut Inflorescence Sap) - Gopal, Murali; Shil, Sandip; Gupta, Alka; Hebbar, K. B.; Arivalagan, M. (Frontiers in Microbiology, 2021)
The phloem sap tapped from unopened inflorescence (spadix) of coconut palm using a novel collecting device ‘Coco-sap chiller’ has been branded Kalparasa® (henceforth as Kalparasa in text) to distinguish its properties not found in sap harvested by traditional methods. To know its hitherto unidentified microbiome profile, we employed high-throughput sequencing to uncover the bacteriome and mycobiome in fresh and 12 hours fermented samples. Fresh Kalparasa had pH of 7.2 which dropped to 4.5 after 12 hours signifying fermentation of the sap. Diversity analysis indicated fresh Kalparasa having higher bacterial species than fermented sample. Contrary to this, fresh sap had lower fungal/yeast diversity than fermented sample. Fresh Kalparasa had relatively higher abundance of probiotic-type Leuconostoc genus followed by equal proportions of Gluconobacter, Acetobacter and Fructobacillus. Twelve hours fermented sample showed a significant increase in Gluconobacter with a sharp decrease in Leuconostoc. Mycobiome data revealed fresh Kalparasa to be preponderant in Saccharomyces and Hansanieospra genera of yeasts while the fermented sap had higher representation of Hansaniespora and Cortinarius and lesser Saccharomyces. This suggested that the fermentation of Kalparasa was probably driven by symbiotic culture of bacteria and yeasts (SCOBY), particularly, acetic acid bacteria and non-saccharomyces yeasts. The bacteriome-function predictions highlighted the enrichment of glycerophospholipd, ABC transporters, purine and pyramidine metabolisms. Based on our findings, Kalparasa containing large population of L. mesenteroides, F. fructosus, S. cereviaseae and H. guilliermondii can be promoted as healthy ‘unfermented’ plant edible food containing live probiotic-type microbiome during its consumption.